The importance of women’s status for child nutrition in developing countries - Smith, Lisa C.; Ramakrishnan, Usha; Ndiaye, Aida; Haddad, Lawrence J.; Martorell, Reynaldo (International Food Policy Research Institute, 2003)
Malnutrition affects one out of every three preschool-age children living in developing countries.This disturbing, yet preventable, state of affairs causes untold suffering and, given its wide scale, presents a major obstacle to the development process.Volumes have been written about the causes of child malnutrition and the means of reducing it. But the role of women’s social status in determining their children’s nutritional health has gone largely unnoticed until recently. This study explores the relationship between women’s status and children’s nutrition in three developing regions: South Asia, Sub-Saharan Africa (SSA), and Latin America and the Caribbean (LAC)." -- from text